2014
DOI: 10.1097/qai.0000000000000118
|View full text |Cite
|
Sign up to set email alerts
|

Burden of HIV Infection Among Children Aged 18 Months to 14 Years in Kenya

Abstract: Backgrounds In Kenya, mathematical models estimate that there are approximately 220,000 children aged less than 15 years infected with HIV. We analyzed data from the second Kenya AIDS Indicator Survey (KAIS 2012) to estimate the prevalence of HIV infection among children aged 18 months to 14 years. Methods KAIS 2012 was a nationally representative 2-stage cluster sample household survey. We studied children aged 18 months to 14 years whose parents or guardians answered questions pertaining to their children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
(18 reference statements)
1
12
1
Order By: Relevance
“…19 Among adults and adolescents aged 15–64 years, the prevalence of HIV was 5.6%, representing an estimated 1,192,000 persons living with HIV, 106,000 of which were new HIV infections. 20 This estimate was significantly lower than that reported in 2007 when the prevalence of HIV, excluding North Eastern region, was 7.2% ( P = 0.002).…”
Section: Kenya Aids Indicator Survey 2012mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Among adults and adolescents aged 15–64 years, the prevalence of HIV was 5.6%, representing an estimated 1,192,000 persons living with HIV, 106,000 of which were new HIV infections. 20 This estimate was significantly lower than that reported in 2007 when the prevalence of HIV, excluding North Eastern region, was 7.2% ( P = 0.002).…”
Section: Kenya Aids Indicator Survey 2012mentioning
confidence: 99%
“…Only 11 of 28 HIV-infected children in KAIS 2012 had been diagnosed previously, and although all children with previous diagnosis were accessing care, only 8 were receiving ART, and of those, only half had achieved viral suppression. 19 …”
Section: Kenya Aids Indicator Survey 2012mentioning
confidence: 99%
“…The MTCT rate was estimated in 2012 to be 15%, accounting for 13,000 new childhood infections in Kenya annually 9, 10. In 2012, the Kenya Ministry of Health adopted international guidelines recommending that repeat HIV testing be offered three months after an initial negative HIV test result in early pregnancy 11.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has found that HIV infection progresses slowly among some infants and a substantial proportion of HIV positive survive to adolescence and beyond. 13,14 Moreover, recent research in Kenya 15 and Ethiopia 16 has found substantial HIV prevalence for older children (under age 15), the majority of whom were presumably not infected through sexual transmission due to low rates of sexual activity for these age groups. In addition, an intervention to reduce HIV among Zimbabwean adolescents had no impact on orphan HIV disparities, leading the authors to suggest that excess risk among orphans is likely due to maternal transmission.…”
mentioning
confidence: 99%
“…16 As a result, many of these HIV positive children are undiagnosed and not linked to treatment. 15,16 As these “missing children” mature into adolescents, they may alter the future course of the HIV epidemic. The goal of this study is to clarify the etiology of orphan HIV disparities, and in doing so provide essential guidance for our response.…”
mentioning
confidence: 99%